Heart injury from gunshot wound to the gluteal region - Cassinelli, Daniel; Kamaid, Emil (Cirugía del Uruguay, 1975)
A case is described whereby a cardiac wound was caused by a bullet which entered the body through the left gluteal region, and passed through the parietal layers of the abdomen without entering the peritoneal cavity_ This produced an acute hemopericardium due to a transfixiant wound in the lower border of the right ventricle, which was successfully repaired through a left anterolateral thoracotomy. An immediate laparotomy confirmed the absence of intra-abdominal lesions. Long term evolution was satisfactory. The course followed by the bullet is explained by the position of the patient at the time he received the shot.